PENGETAHUAN DAN SIKAP MAHASISWA DENGAN PRA MENSTRUASI SINDROM - Rizka Angrainy; Rika Istawati; Monifa Putri (Institut Kesehatan dan Teknologi Al Insyirah, 2023)
Pre Menstrual Syndrome (PMS) is broadly defined as a recurring disorder around 67% of female students who experience premenstrual syndrome disorder is the most disturbing complaint that reduces the quality of learning by up to 50%, around 14% of women between the ages of 20 to 35 years, pre Menstrual syndrome can greatly affect the effect so that it requires them to rest, the premenstrual syndrome will disappear after menstruation is over and due to the lack of knowledge of respondents in understanding the signs and symptoms of premenstrual syndrome. This study aims to determine the relationship between the knowledge and attitudes of female students with premenstrual syndrome (PMS) to find out the signs and symptoms of premenstrual syndrome as early as possible. This type of research uses quantitative analytic methods, with a cross-sectional design, the total population from levels I, II, and III is 228 people, and a sample of 69 people is obtained by accidental sampling technique. Of the 69 respondents who showed good knowledge and did not experience premenstrual syndrome, 18 people (59.9%) were good and 16 (47.1%) experienced premenstrual syndrome. (50.2%) and experienced premenstrual syndrome in 24 people (50.2%). Based on the chi-square test, a p-value of 0.000 was obtained, which means that p <0.05 there is a relationship between female students' knowledge and premenstrual syndrome, p<0.032. There is a significant relationship between student attitudes and premenstrual syndrome.